A thermal circuit model consistent with integral energy balance for internal forced convection in a circular tube. (August 2015) - Ho, C.J.; Huang, Chao-Sheng; Viskanta, R.
Highlights: A thermal circuit for internal forced convection in a circular tube is developed. Heat transfer path between tube wall and inlet fluid is described analytically. Inlet fluid temperature should be based to define the convection coefficient. Abstract: The equivalent thermal resistance circuit based on integral energy balance of thermally developing forced convection in a circular tube is derived describing the heat flow path between the heated tube wall and inlet fluid. The axial heat conduction of the flow is assumed to be negligibly small. To validate the thermal circuits developed, numerical simulations have been performed for laminar thermally developing forced convection of water in a circular tube with an imposed constant heat flux or constant wall temperature. The overall thermal resistances for the convective circuit separating the heated tube wall and inlet fluid are simply the convection thermal resistances due to the local/average heat transfer coefficients, respectively, defined based on the difference between local/average tube wall temperature and inlet fluid temperature. Applications of the convection thermal circuit derived have been demonstrated for direct or indirect evaluation of the pertinent heat transfer parameters of technical interest characterizing the forced convection heat transfer of thermally developing fluid flow in the iso-flux or iso-thermally heated tube.